Desenvolvimento de um índice de integridade biótica para riachos do Alto rio Tocantins - Ávila, Milton Pereira de (2015)
The objective of this study was to develop an index of biotic integrity (IBI) using fish for evaluation streams of the upper rio Tocantins basin, sub-basin of the river Santa Teresa, in the northern region of Goiás. We selected transects of 80 meters 16 streams 1st and 2nd order, the sub-basin of the river Santa Teresa to develop the study. We collected 4,079 individuals distributed in 5 orders, 12 families and 30 species. Fifty-six metrics were initially listed to compose the index and after the sensitivity and redundancy, tests left five metrics that distinguish degraded streams of conserved streams. The validation of the IIB was made with the application of the metrics in the streams considered intermediate, which achieved a score at the boundary between conserved environments and degraded as expected. The fact that some metrics show peculiar behavior to the environment studied and contrary to previous similar work demonstrates the importance of regional adaptation of such a tool for a more reliable and effective result.